Stability: A key issue for self-assembled monolayers on gold as thin-film coatings and nanoparticle protectants - Srisombat L. (2014)
This review examines the use of self-assembled monolayers (SAMs) on gold as nanoscale protective coatings for both nominally flat substrates and for nanoparticles. The thermal and chemical stabilities of the SAMs are discussed, and the various strategies used by researchers to generate thin films with enhanced resistance to corrosion and/or decomposition are described. The use of multidentate adsorbates to achieve the desired objectives is emphasized. © 2011 Elsevier B.V.